(untitled) (Biological Sciences - PJSIR, 2023)
Salinity stress is one of the most serious environmental factors adversely affects plant growth and yield in Pakistan and around the world. Little millet (Panicum colonum L.) is an important cereal crop which is principal source of food and is extensively grown in Pakistan and other areas of the world. The pot experiment was carried out in CRD design with six treatments including control contained three replications in the Department of Food Science and Technology, Hamdard University Karachi. Plants of Little millet (Panicum colonum L.) watered as 00 mM control, 120 mM of each NaCl, MgCl2, CaCl2, mixture of salts and natural salt concentrations. The overall osmotic potential increased by about 57% on 120 (mM) concentration of mixture of salts. Satisfactory K+/Na+ ratio was obtained from 120 mM of CaCl2 treatment, sufficient Ca2+ (mM) content was noted in 120 mM of mixture of salts treatment in the cell sap of (Panicum colonum L.) leaves as compared to other treatments and control, respectively. However, increased osmotic potential about 58 and 88% on 120 mM of mixture of salts and natural salt, such condition of osmotic potential under various chloride stress conditions for little millet (Panicum colonum L.) claimed to be stress tolerant.